2016
DOI: 10.1038/srep25728
|View full text |Cite
|
Sign up to set email alerts
|

Calcium influx through TRP channels induced by short-lived reactive species in plasma-irradiated solution

Abstract: Non-equilibrium helium atmospheric-pressure plasma (He-APP), which allows for a strong non-equilibrium chemical reaction of O2 and N2 in ambient air, uniquely produces multiple extremely reactive products, such as reactive oxygen species (ROS), in plasma-irradiated solution. We herein show that relatively short-lived unclassified reactive species (i.e., deactivated within approximately 10 min) generated by the He-APP irradiation can trigger physiologically relevant Ca2+ influx through ruthenium red- and SKF 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…As Privat-Maldonado et al showed through electroparamagnetic spectroscopy, there are also increases in the concentrations of short-lived species after plasma treatment of cell culture medium [45], which are precursors to these long-lived species [44]. The biological effects of the short-lived species on cellular responses are well-documented in plasma literature [15,35,54]. These initiating molecules are absent during mock treatments, which is why we did not observe similar cellular responses and GSH modifications to plasma treatment.…”
Section: Gsh Modifications Unique To Plasma Source Indicate the Stresmentioning
confidence: 96%
“…As Privat-Maldonado et al showed through electroparamagnetic spectroscopy, there are also increases in the concentrations of short-lived species after plasma treatment of cell culture medium [45], which are precursors to these long-lived species [44]. The biological effects of the short-lived species on cellular responses are well-documented in plasma literature [15,35,54]. These initiating molecules are absent during mock treatments, which is why we did not observe similar cellular responses and GSH modifications to plasma treatment.…”
Section: Gsh Modifications Unique To Plasma Source Indicate the Stresmentioning
confidence: 96%
“…We also employed the indirect plasma irradiation (IPI) and focused on the interaction between reactive species and cell membrane proteins, because the first contact of reactive species with cells is thought to be just with membrane lipids or membrane proteins. We experimentally showed that relatively short‐lived reactive species (i.e., deactivated within approximately 10 min) in APP‐irradiated solution could activate transient receptor potential (TRP) channel family member(s) and induce physiologically relevant calcium (Ca 2+ ) influx, which plays key roles in many cellular processes . Regarding APP‐induced anti‐cancer effects, Yan et al reported that knockdown of aquaporin‐8 significantly inhibited the anti‐cancer capacity of APP‐irradiated medium .…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA present at the surface of EVs can modify the ability of EVs to interact with the ECM, whereas oncogenes transferred as single-or double-stranded DNA can increase the production of specific proteins (such as those involved in the response to oxidative stress) in the recipient cells [202]. influx through TRP channels [203]. Induced Ca 2+ release by ER* and mitochondria needed to induce senescence in melanoma cells [204] ROS affect channel function, structure and downstream signalling pathways [205].…”
Section: Cell-to-cell Communicationmentioning
confidence: 99%